Analisa Performa Turbin Gas Unit 1 pada Pembangkit Listrik Tenaga Gas PT A Kepri - Jon, Rahmat Novri; Atabiq, Fauzun (Politeknik Negeri Batam, 2023)
Abstract—The research in this final project is focused on analyzing ther performance of gas turbines. The gas turbine power plant is analyzed using the technical data of the plant. The data used in this study were obtained from the PLTG PT A Kepri. The research methodology is based on qualitative and quantitative research. The result of the analysis in this study are for a period of six months (April-September) 2022. This study shows that 87% of the expected capacity is available in the period studied. Plant Thermal effeciency ranged from 23% to 28%, Plant Capacity Factor ranged from 61% to 81%, and plant reliability ranged from 46% to 100% (averange 75,5%). For the period studied only 27 MW of power was lost from the expected power of 210 MW. In this study, the gas turbine performance parameter analyzed at PLTG PT A Kepri are within the best industry practice range.